Pengaruh Perilaku Organisasi dan Penerapan Standar Akuntansi Pemerintahan terhadap Sistem Keuangan Desa - Gusasi, Suwardi; Saprudin, Saprudin; Masiaga, Novaliastuti; Abdullah, Julie; Junus, Onong (Universitas Gorontalo, 2025)
This study aims to analyze the influence of organizational behavior and the implementation of government accounting standards on the village financial system (SISKEUDES) in Gorontalo Regency. The research employs a quantitative approach by involving village treasurers as respondents. The findings reveal that organizational behavior does not have a significant effect on the village financial system. This condition is suspected to be related to non-compliance with procedures, lack of transparency, and weak coordination within the village organization. On the other hand, the implementation of government accounting standards has a positive effect on the village financial system. This indicates that a good understanding of accounting standards by village officials can encourage the preparation of more accurate, transparent, and accountable financial reports.